Kontribusi Public Relations dalam Implementasi Program CSR (Corporate Social Responsibility) - Negoro, Sherly Negoro Hindra (Interaksi: Jurnal Ilmu Komunikasi, 2014)
The topic of CSR is very interesting to be studied. CSR has been duty and should be done by company. Implementation for the activities is various based on planned by company. Public Relations (PR) has a significantrole to develop this program. As a bond between public and company, PR put CSR activities into the program as a part of community relations. In fact, the company not only put this program as a part of community relations but was developed by complex activities. This paper is using shutter literature to understand that topic.